Deafness in dogs and cats [ - Strain, George M. (CABI, 2011)
Deafness in pets is a very common problem and is increasingly being presented to veterinarians, as owners and breeders become more aware and concerned about such issues. This book will provide complete coverage of the subject describing the anatomy and hysiology of the auditory system, types of deafness, testing for deafness, methods of amelioration and management, behaviour of deaf animals, and other issues associated with living and dealing with deaf pets.